Wooden Cube Puzzle as an Effort to Introduce Traditional Nusantara Clothing and Houses - Patria, Asidigisianti Surya; Martadi, Martadi; Kristiana, Nova; Anggalih , Nanda Nini; Carreca, Irhamna Nirbhaya; Laksmi, Arieviana Ayu; Nurcahyanie, Yunia Dwie (Bina Nusantara University, 2025)
Indonesia is rich in cultural heritage, and introducing local culture is essential for shaping a child's identity, particularly among the younger generation. However, there is a lack of engaging educational media to introduce Indonesian cultural heritage to young students. Existing materials often fail to support the development of cognitive and motor skills, and they frequently do not utilize safe and sustainable materials. Therefore, innovation is needed to instill traditional values in future generations. The research aims to design a wooden puzzle that allows children to learn through play while gaining a deeper understanding of Indonesia's cultural heritage. The research employs research and development methods, including literature reviews and in-depth interviews. Experts validated the puzzle through interviews and questionnaires with teachers to ensure it was suitable for children. The puzzles were designed in a cheerful and simple cartoon style, focusing on traditional clothing and houses. Teachers rated the puzzle's validity at 99.28%, indicating that it meets educational standards and helps students understand cultural diversity. Students gave a validation score of 97.75% based on the questionnaire criteria. The research emphasizes the effectiveness of wooden cube puzzles as an interactive learning tool that offers advantages over other similar products for introducing Nusantara's traditional clothing and houses to elementary students. The findings suggest that this puzzle can enhance student engagement and cultural awareness. Its effectiveness can be further improved through digital integration for a greater educational impact. Overall, the research concludes that using wooden cultural puzzles can effectively enhance children's cognitive skills while fostering cultural awareness and national identity.